The Determinants of Smallholder Farmers on the Functionality of Plant Health Clinics in the Vhembe District, South Africa - Maanda Rambauli; Michael Akwasi Antwi; Phumudzo Patrick Tshikhudo; Fhatuwani Nixwell Mudau (Agriculture, 2023)
A plant health clinic is a system in which under-resourced and smallholder farmers can access basic services of plant healthcare from a plant clinic in relation to infected or symptomatic plants and plant products for pest diagnostic and identification purposes. The factors that influence smallholder farmers’ awareness and accessibility to plant health clinics in the Vhembe District Municipality of Limpopo Province, South Africa were examined in this study. The study also identified the constraints of the plant clinics that prevent their effective utilization. Three-hundred and twenty smallholder farmers (n = 320) from the population of 1600 were interviewed through a semi-structured questionnaire. A multistage random sampling technique was employed to select the 320 smallholder farmers from 8 irrigation schemes in the study area. To ensure representation, all categories of smallholder farmers were included in the study. Descriptive statistics such as frequency and percentages and Logit regression model were employed for the data analyses. The results revealed that there is a statistically significant and positive relation between communication channels and plant clinics awareness and accessibility among smallholder farmers. The distance to plant clinics has a negative influence on the accessibility of plant clinics among the farmers; however, the accessibility of plant clinic improves when visits by extension officers or plant doctors to farmers increase. The study pointed out some challenges affecting the functionality of plant clinics, which could be resolved through an efficient and effective plant clinic framework that involves major role players. An efficient and effective plant clinic framework was therefore developed by the study to improve its usefulness for diagnosing plant pest symptoms and diseases. The study concluded that plant clinic framework was important and should be considered and adopted by policy makers within the government, research institutes, and other NGOs.